Online Learning Innovations in School: Case Study on Subject Teacher Conference of Junior High School Pancasila and Civic Education in Surabaya City - Harmanto; Oksiana Jatiningsih; Listyaningsih; Siti Habinah (Studies in Learning and Teaching, 2023)
This research aims to discover how the Pancasila and civic education learning practices at junior high schools in Surabaya during the COVID-19 pandemic. The method this research uses is a quantitative approach with a survey design. The findings from this research are teachers and students are not ready for WFH and LFH. So, teachers use various channels in learning. For example, WhatsApp Group, Zoom, Google Classroom, and others. From this research, conclusions can be drawn, including (1) With the pandemic conditions requiring teachers to be able to adapt, from respondents who felt 13.5% less capable before the pandemic in mastering online learning, teachers were finally able to adjust supportive learning technology; (2) Mastery of teachers in online learning before the pandemic period resulted in very capably 7.9%, capable 78.7%, underprivileged 13.5%, unable 0%. The additional cost of internet access during online learning is between IDR 25,000 to IDR 100,000/month. This research novelties are tended to discuss the teachers’ readiness in Junior High School to Pancasila and civic education limited to Surabaya city.